Gene Therapy: A step toward advanced orthodontics – A narrative review - Monika Shukla; Shalu Jain; C. Munish Reddy; Pradeep Raghav; Kumar Amit; Rinchin Yangzom; Shivika Garg; Aastha Kamrani (SRM Journal of Research in Dental Sciences)
Background: Gene therapy deals with the insertion of exogenous genes into a cell to produce the desired therapeutic effect. After the introduction of gene therapy in dentistry, this field is also flourishing rapidly in the branch of orthodontics and dentofacial orthopedics as it can prevent many prenatal and postnatal dentofacial anomalies which have the genetical etiology. Despite various animal studies showing promising results, a lot more is left to be explored. Aim: This narrative review was conducted to understand the role of gene therapy for various orthodontic procedures and its future scope. Methods: Research publications were searched on search engines such as Scopus, PubMed, and Google Scholar, and articles with terms such as “gene therapy, orthodontic tooth movement (OTM), condylar growth, and bone repair” were collected. Results: A total of 40 articles were collected and they were further used to formulate this review. Discussion: Gene therapy was found to have a major role in orthodontics, especially for: (i) Modulation in OTM, (ii) Alleviation of orthodontic pain, (iii) Enhancement of bone repair and regeneration, (iv) Improving midface hypoplasia by preventing syndromic craniosynostosis, and (v) Modifying condylar growth.